Evaluation of gadolinium-EOB-DTPA uptake after portal vein embolization: value of an increased flip angle. (March 2014) - Geisel, Dominik; Lüdemann, Lutz; Wagner, Clemens; Stelter, Lars; Grieser, Christian; Malinowski, Maciej; Stockmann, Martin; Seehofer, Daniel; Hamm, Bernd; Gebauer, Bernhard; Denecke, Timm
Background: The optimal sequence for Gd-EOB-DTPA uptake measurement in the liver with the purpose of liver function measurement is still not defined. Purpose: To prospectively evaluate the effect of an increased flip angle (FA) of a T1-weighted fat-saturated 3D sequence for the measurement of hepatocyte uptake of Gd-EOB-DTPA magnetic resonance imaging (MRI) after right portal vein embolization (PVE). Material and Methods: Ten patients who received a PVE prior to an extended hemihepatectomy were examined 14 days after PVE using Gd-EOB-DTPA enhanced MRI of the liver using the standard FA of 10° and the increased FA of 30°. Results: Relative enhancement of the right liver lobe (RLL) was 0.52 ± 0.12 for 10° and 1.41 ± 0.39 for 30°. Relative enhancement of the left liver lobe (LLL) was 0.58 ± 0.11 for 10° and 2.05 ± 0.61 for 30°. Relative enhancement of the RLL was significantly higher for 30° than for 10° ( P = 0.009) and significantly higher in the 30° than in the 10° sequences ( P = 0.005) for the LLL. Conclusion: A flip angle of 30° increases the contrast between liver partitions with and without portal venous embolization. Thereby, the sensitivity for differences in uptake intensity is increased. This could be of value for a more exact determination of differences in regional liver function and, consequently, the estimation of the future remnant liver function.